2013
DOI: 10.1016/j.otsr.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar-pelvic-femoral balance on sitting and standing lateral radiographs

Abstract: Trunk balance in upright stance expresses an individual postural strategy found on anatomic and functional parameters. The "pelvic vertebra" is an essential transitional region for the coherence of spinal parameters (notably, lumbar lordosis and thoracic kyphosis) and pelvic parameters (sacral slope, pelvic tilt and incidence). Deterioration of this postural harmony is often associated with spinal aging, maladjusted spinal arthrodeses, or mechanical abnormalities of the hip joints. Spinal surgeons are aware of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 28 publications
6
100
0
6
Order By: Relevance
“…Previous studies have measured pelvic tilt in patients undergoing THA during sitting and standing positions, usually reporting values similar to ours with mean standing sacral slope angles between 35°and 40°, and mean sitting sacral slope angles between 14°and 24° [19,22,26]. Our study is the first, to our knowledge, to stratify patients undergoing THA into those with or without lumbar DDD, and we found that most patients with DDD had flattened backs (mean 7°less lumbar lordosis) and more posterior pelvic tilt (mean 5°more sacral slope) in standing.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Previous studies have measured pelvic tilt in patients undergoing THA during sitting and standing positions, usually reporting values similar to ours with mean standing sacral slope angles between 35°and 40°, and mean sitting sacral slope angles between 14°and 24° [19,22,26]. Our study is the first, to our knowledge, to stratify patients undergoing THA into those with or without lumbar DDD, and we found that most patients with DDD had flattened backs (mean 7°less lumbar lordosis) and more posterior pelvic tilt (mean 5°more sacral slope) in standing.…”
Section: Discussionsupporting
confidence: 80%
“…This may not replicate how patients sit comfortably during their daily activities. However, previous studies used the same method [22,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations